Mono-mesoporous silica nano bowl and preparation method thereof
Through a stable single micelle assisted interface assembly method, ultra-small single mesoporous silica nanobowls were synthesized, which solved the problems of uneven nanoparticles and insufficient pore structure in the traditional method, and achieved the high specific surface area of the material and Excellent hydrophobic properties.
Patent Information
- Application Number
- CN202510046636.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to synthesize ultra-small single mesoporous bowl-shaped nanoparticles in the prior art, and the nanoparticles synthesized by traditional methods are uneven in size and insufficient pore structure, which limits their application in energy storage, adsorption, catalysis and other fields.
Using a stable single micelle assisted interface assembly method, a spherical single micelle aqueous solution with a bilayer structure is formed by mixing block copolymer F127 with aqueous hydrochloric acid solution, and the addition of 1,3,5-trimethylbenzene and prosilicon Compounds such as tetraethyl acid ester gradually form monomesoporous silica nanobowls with rich methyl groups on the surface.
The ultra-small, uniform single mesoporous silica nanobowl was successfully synthesized, with unique open pores and a large number of surface micropores, significantly improving the specific surface area and chemical reactive sites of the material, enhancing its hydrophobicity and resistance. Corrosion performance.
Smart Images

Figure CN119461399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and more specifically, to a single mesoporous silica nanobowl and a preparation method thereof. Background Art
[0002] Bowl-shaped materials are often widely used in research fields such as energy storage, adsorption, catalysis, energy, and biomedicine because of their many excellent properties, such as high active surface interface, large pore volume, unique pore structure, and smooth material transfer channels. The morphology of bowl-shaped materials synthesized using traditional template-free methods, hard template methods, and nanoemulsion methods is often uncontrollable. This uncontrollability makes their number, size, pore size, and thickness extremely uneven, and even causes irregular aggregation and severe deformation of nanoparticles. Most of them have few mesoporous structures and are too large in size, usually at the micron level, which limits their practical application to a certain extent. For example, patent No. CN202110263736.8 discloses a method for preparing a silica nanobowl, and the size of the prepared silica nanobowl is about 300 nm. So far, there has been no report on the synthesis of ultra-small single mesoporous bowl-shaped nanoparticles. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a single mesoporous silica nanobowl and a preparation method thereof. The single mesoporous silica nanobowl and the preparation method thereof provided by the present invention utilize a stable single micelle-assisted interface assembly method to synthesize an ultrasmall single mesoporous silica nanobowl, thereby solving the problem of synthesizing ultrasmall asymmetric hollow mesoporous structure materials. The prepared single mesoporous silica nanobowl has an ultrasmall and uniform size, and its unique open channels and a large number of surface micropores greatly improve the specific surface area of the material and increase the active sites of chemical reactions. Its surface contains abundant methyl groups, which makes the material super hydrophobic and corrosion-resistant.
[0004] To achieve the above object, the present invention provides the following technical solution: a single mesoporous silica nanobowl, wherein the single mesoporous silica nanobowl is a hollow structure, the particle size of the single mesoporous silica nanobowl is 20-40 nm, and the specific surface area is 500-800 m 2 / g, and the size of the concave pores on the surface of the single mesoporous silica nanobowl is 10-25 nm.
[0005] Another aspect of the present invention provides the following technical solution: a method for preparing a single mesoporous silica nanobowl, comprising the following steps: (1) The block copolymer F127 (PEO-PPO-PEO) and a 1-5 mol / L hydrochloric acid aqueous solution are uniformly mixed at a mass ratio of 1:30-100. The hydrophobic PPO ends are automatically aggregated in the inner layer due to their insolubility in the hydrochloric acid aqueous solution, while the hydrophilic PEO ends are distributed in the outer layer due to their good compatibility with the hydrochloric acid aqueous solution, forming a double-layer structured spherical single micelle aqueous solution; (2) 1,3,5-trimethylbenzene (TMB) is mixed with the single micelle aqueous solution prepared in step (1) and stirred for 14-36 hours at a stirring speed of 800-1500 r / min. Due to the principle of like dissolves like, TMB in the oil phase will enter the hydrophobic end PPO region inside the single micelle aqueous solution, thereby swelling the polymer single micelle to obtain a TMB@PEO-PPO-PEO single micelle composite solution; (3) Add tetraethyl orthosilicate (TEOS) to the TMB@PEO-PPO-PEO single micelle composite solution prepared in step (2), and stir at a speed of 800-1500 r / min for 5-24 h to obtain a core-shell structure TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution with hydroxyl groups on the surface; The specific reaction chemical formula of step (3) is as follows:
[0006] (4) Adding dimethyldimethoxysilane (DMDMS) as a capping agent to the TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution prepared in step (3), stirring at a speed of 800-1500 r / min for 12-36 h, to obtain a TMB@PEO-PPO-PEO@SiO2 organic-inorganic hybrid composite material solution with abundant methyl groups on the surface; The specific reaction chemical formula of step (4) is as follows:
[0007] (5) The composite material solution of step (4) is volatilized to remove 1,3,5-trimethylbenzene in the composite material solution, followed by centrifugation and washing; the obtained sample is then refluxed in anhydrous ethanol to remove the block copolymer, and finally dried to obtain a single mesoporous silica nanobowl.
[0008] Furthermore, the mass ratio of the 1,3,5-trimethylbenzene in step (2) to the block copolymer F127 in step (1) is 1:0.33-10.
[0009] Furthermore, the mass ratio of the tetraethyl orthosilicate in step (3) to the block copolymer F127 in step (1) is 1:0.33-10.
[0010] Furthermore, the mass ratio of the dimethyldimethoxysilane in step (4) to the block copolymer F127 in step (1) is 1:0.17-5.
[0011] Furthermore, in step (5), the reaction mixture is volatilized at room temperature for 12-48 hours.
[0012] Furthermore, the centrifugal speed in step (5) is 30000-80000 r / min, and the centrifugal time is 10-30 min.
[0013] Furthermore, the washing conditions in step (5) are to first use distilled water for 3 times, and then use 95% ethanol solution for 3 times.
[0014] Furthermore, the reflux temperature in step (5) is 50-90°C, and the reflux time is 0.5-5 h.
[0015] The advantages of the present invention are: 1. The present invention discloses a single mesoporous silica nanobowl and a preparation method thereof. An ultra-small single mesoporous silica nanobowl is synthesized by a stable single micelle-assisted interface assembly method, which solves the difficulty in synthesizing ultra-small asymmetric hollow mesoporous structure materials. The prepared single mesoporous silica nanobowl has an ultra-small and uniform size, and the unique open channels and a large number of surface micropores greatly improve the specific surface area of the material and increase the active sites of chemical reactions.
[0016] 2. The present invention discloses a single mesoporous silica nanobowl with a surface opening size of about 17 nm, a particle size of about 32 nm, and a specific surface area of up to 519 m 2 / g, with excellent dispersibility and uniformity, and its surface contains abundant methyl groups, which makes the material have good hydrophobic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of the single mesoporous silica nanobowl prepared in Example 1 of the present invention.
[0018] Figure 2 This is a transmission electron microscope image of the single mesoporous silica nanobowl prepared in Example 1 of the present invention.
[0019] Figure 3 This is the infrared test spectrum of the single mesoporous silica nanobowl prepared in Example 1 of the present invention.
[0020] Figure 4 This is a scanning electron microscope image of the single mesoporous silica nanobowl prepared in Example 2 of the present invention.
[0021] Figure 5 This is a scanning electron microscope image of the single mesoporous silica nanobowl prepared in Example 3 of the present invention.
[0022] Figure 6 This is a scanning electron microscope image of the single mesoporous silica nanobowl prepared in Example 4 of the present invention.
[0023] Figure 7 This is a scanning electron microscope image of the single mesoporous silica nanobowl prepared in Example 5 of the present invention.
[0024] Figure 8 This is a hydrophobic angle diagram of a single mesoporous silica nanobowl coated with a bare zinc sheet and a bare zinc sheet prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.
[0027] In the present invention, unless otherwise specified, the directions used, such as "up" and "down", usually refer to the directions shown in the drawings, or to the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "left" and "right" usually refer to the left and right shown in the drawings; "inside" and "outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directions are not used to limit the present invention.
[0028] Example 1: A method for preparing a single mesoporous silica nanobowl, comprising the following steps: (1) 0.3 g of block copolymer F127 (PEO-PPO-PEO) was mixed evenly with 15 mL of 2 mol / L hydrochloric acid aqueous solution to form a double-layer spherical single micelle aqueous solution; (2) Add 0.3 g of 1,3,5-trimethylbenzene (TMB) to the single micelle aqueous solution prepared in step (1), mix and stir for 14 h at a stirring speed of 1400 r / min to obtain a TMB@PEO-PPO-PEO single micelle composite solution; (3) Add 0.3 g of tetraethyl orthosilicate (TEOS) to the TMB@PEO-PPO-PEO single micelle composite solution prepared in step (2), and stir at a speed of 1400 r / min for 8 h to obtain a core-shell structure TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution with hydroxyl groups on the surface; (4) 0.1 g of dimethyldimethoxysilane (DMDMS) was added as a capping agent to the TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution prepared in step (3), and the mixture was stirred at 1400 r / min for 24 h to obtain a TMB@PEO-PPO-PEO@SiO2 organic-inorganic hybrid composite material solution having abundant methyl groups on the surface; (5) The composite material solution of step (4) was volatilized at room temperature for 24 h to remove 1,3,5-trimethylbenzene in the composite material solution. The composite material solution was then centrifuged at 80,000 r / min for 15 min, followed by washing with water three times and washing with 95% ethanol three times. Finally, the obtained sample was refluxed in anhydrous ethanol at 80°C for 1 h to remove the block copolymer, and finally dried to obtain a single mesoporous silica nanobowl.
[0029] The single mesoporous silica nanobowl prepared in Example 1 was observed for microstructure by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 and Figure 2 As shown, the size, thickness and pore size of the single mesoporous silica nanobowl prepared in this embodiment are uniform; Figure 1 It can be seen that the particle size of the prepared ultra-small bowl-shaped particles is 20-40 nm, and the specific surface area is 519 m 2 / g, and showed good dispersion. A concave mesopore can be found in the center of each particle. In addition, a considerable number of nanoparticles were successfully observed to be in a state where the mouth of the bowl was facing away from the field of view, mainly showing the back of the bowl (the convex part). Figure 2 It can be seen that the overall morphology of the particles is a hollow bowl-shaped structure. After measurement, the thickness of the hollow shell is about 7 nm, and the pore size of the concave mesopores is about 17 nm.
[0030] The single mesoporous silica nanobowl prepared in Example 1 was prepared by tabletting to prepare a sample, and infrared spectroscopy was performed. The results are as follows: Figure 3 As shown, from Figure 3 The FT-IR spectrum shows that the −1 The absorption band at 400 nm can be attributed to the vibration of the C−H bond in the -CH3 group, indicating the presence of a methane-bridging skeleton.
[0031] Example 2: The overall method is the same as that of Example 1, except that the amount of 1,3,5-trimethylbenzene (TMB) added in step (2) is 0.5 g.
[0032] The single mesoporous silica nanobowl prepared in Example 2 was observed for microstructure by scanning electron microscopy (SEM). Figure 4 As shown, from Figure 4 It can be seen that the particle size of the prepared ultra-small bowl-shaped particles is 20-40 nm, and the specific surface area is 612 m 2 / g, the pore size of the depressed mesopores is about 22-25 nm, and the pore size of the depressed mesopores is larger than that of Example 1. This is because when the amount of TMB increases, more TMB molecules will occupy the space inside the mesopores, thereby expanding the size of the mesopores.
[0033] Example 3: The overall method is the same as that of Example 1, except that the amount of tetraethyl orthosilicate (TEOS) added in step (3) is 0.5 g.
[0034] The single mesoporous silica nanobowl prepared in Example 3 was observed for microstructure by scanning electron microscopy (SEM). Figure 5 As shown, from Figure 5 It can be seen that the particle size of the prepared ultra-small bowl-shaped particles is 20-40 nm, and the specific surface area is 510 m 2 / g, the pore size of the depressed mesopores is 12-17nm, which is smaller than that in Example 1. The overall structure shows obvious agglomeration, indicating that the precursors excessively aggregate and react in local areas to form agglomerated silica. More silica accumulates around the template and fills the space where larger mesopores could have been formed.
[0035] Example 4: A method for preparing a single mesoporous silica nanobowl, comprising the following steps: (1) 0.3 g of block copolymer F127 (PEO-PPO-PEO) was mixed evenly with 9 mL of 1 mol / L hydrochloric acid aqueous solution to form a double-layer spherical single micelle aqueous solution; (2) Add 0.1 g of 1,3,5-trimethylbenzene (TMB) to the single micelle aqueous solution prepared in step (1), mix and stir for 25 h at a stirring speed of 800 r / min to obtain a TMB@PEO-PPO-PEO single micelle composite solution; (3) Add 0.1 g of tetraethyl orthosilicate (TEOS) to the TMB@PEO-PPO-PEO single micelle composite solution prepared in step (2), and stir at a speed of 800 r / min for 5 h to obtain a TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution with a core-shell structure and hydroxyl groups on the surface; (4) 0.05 g of dimethyldimethoxysilane (DMDMS) was added as a capping agent to the TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution prepared in step (3), and the mixture was stirred at 800 r / min for 12 h to obtain a TMB@PEO-PPO-PEO@SiO2 organic-inorganic hybrid composite material solution having abundant methyl groups on the surface; (5) The composite material solution of step (4) was volatilized at room temperature for 12 h to remove 1,3,5-trimethylbenzene in the composite material solution. The composite material solution was then centrifuged at 30,000 r / min for 30 min (the lower the speed, the longer the time required), followed by washing with water three times and washing with 95% ethanol three times; finally, the obtained sample was refluxed in anhydrous ethanol at 50°C for 5 h (the lower the temperature, the longer the time required) to remove the block copolymer, and finally dried to obtain a single mesoporous silica nanobowl.
[0036] The single mesoporous silica nanobowl prepared in Example 4 was observed for microstructure by scanning electron microscopy (SEM). Figure 6 As shown, from Figure 6 It can be seen that the particle size of the prepared ultra-small bowl-shaped particles is 20-40 nm, and the specific surface area is 502 m 2 / g, the pore size of the depressed mesopores is 10-15nm, wherein the pore size of the depressed mesopores is smaller than that of Example 1, thereby resulting in a smaller specific surface area than that of Example 1.
[0037] Example 5: A method for preparing a single mesoporous silica nanobowl, comprising the following steps: (1) 0.3 g of block copolymer F127 (PEO-PPO-PEO) was mixed evenly with 30 mL of 5 mol / L hydrochloric acid aqueous solution to form a double-layer spherical single micelle aqueous solution; (2) Add 3 g of 1,3,5-trimethylbenzene (TMB) to the single micelle aqueous solution prepared in step (1), mix and stir for 36 h at a stirring speed of 1500 r / min to obtain a TMB@PEO-PPO-PEO single micelle composite solution; (3) Add 3 g of tetraethyl orthosilicate (TEOS) to the TMB@PEO-PPO-PEO single micelle composite solution prepared in step (2), and stir at a speed of 1500 r / min for 24 h to obtain a TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution with a core-shell structure and hydroxyl groups on the surface; (4) 1.5 g of dimethyldimethoxysilane (DMDMS) was added as a capping agent to the TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution prepared in step (3), and the mixture was stirred at 1500 r / min for 36 h to obtain a TMB@PEO-PPO-PEO@SiO2 organic-inorganic hybrid composite material solution having abundant methyl groups on the surface; (5) The composite material solution of step (4) was volatilized at room temperature for 48 h to remove 1,3,5-trimethylbenzene in the composite material solution. The composite material solution was then centrifuged at 80,000 r / min for 10 min, followed by washing with water three times and washing with 95% ethanol three times. Finally, the obtained sample was refluxed in anhydrous ethanol at 90°C for 0.5 h to remove the block copolymer, and finally dried to obtain a single mesoporous silica nanobowl.
[0038] The single mesoporous silica nanobowl prepared in Example 5 was observed for microstructure by scanning electron microscopy (SEM). Figure 7 As shown, from Figure 7 It can be seen that the particle size of the prepared ultra-small bowl-shaped particles is 20-40 nm, and the specific surface area is 715 m 2 / g, the pore size of the depressed mesopores is 25-30 nm, wherein the pore size of the depressed mesopores is larger than that of Example 1, and the specific surface area is larger than that of Example 1.
[0039] Experiment: The single mesoporous silica nanobowl material prepared in Example 1 was coated on a zinc sheet, and then a drop of water was dropped on the zinc sheet coated with the material in Example 1 and on the bare zinc sheet without the coating material, and then the hydrophobic angle was measured with a contact angle tester. The results are shown in FIG. Figure 8 ,from Figure 8 It can be seen from (a) that the hydrophobic angle of the zinc sheet coated with the material of Example 1 is 131.57°; Figure 8 It can be seen from (b) that the hydrophobic angle of the bare zinc sheet without coating material is 79.35°; it is obvious that the single mesoporous silica nanobowl material prepared in the present invention has good hydrophobic properties.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0041] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A single mesoporous silica nanobowl, characterized in that: The single mesoporous silica nanobowl is a hollow structure, and the particle size of the single mesoporous silica nanobowl is 20-40 nm, and the specific surface area is 500-800 m 2 / g, and the diameter of the concave pores on the surface of the single mesoporous silica nanobowl is 10-25 nm.
2. The method for preparing a single mesoporous silica nanobowl according to claim 1, characterized in that: It includes the following steps: (1) Preparation of a single micelle aqueous solution: The block copolymer F127 and a 1-5 mol / L hydrochloric acid aqueous solution are mixed uniformly in a mass ratio of 1:30-100 to form a single micelle aqueous solution; (2) Preparing a TMB@PEO-PPO-PEO single micelle composite solution: mixing 1,3,5-trimethylbenzene with the single micelle aqueous solution prepared in step (1) and stirring for 14-36 h at a stirring speed of 800-1500 r / min to obtain a TMB@PEO-PPO-PEO single micelle composite solution; (3) Preparing a TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution: adding tetraethyl orthosilicate to the TMB@PEO-PPO-PEO single micelle composite solution prepared in step (2), stirring at a speed of 800-1500 r / min for 5-24 h to obtain a TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution; (4) Preparing a composite material solution: adding dimethyldimethoxysilane to the TMB@PEO-PPO-PEO@SiO2 composite nanomaterial solution prepared in step (3), stirring at a speed of 800-1500 r / min for 12-36 h to obtain a composite material solution; (5) Preparation of a single mesoporous silica nanobowl: The composite material solution of step (4) is volatilized to remove 1,3,5-trimethylbenzene in the composite material solution, followed by centrifugation and washing; the obtained sample is then refluxed in anhydrous ethanol to remove the block copolymer, and finally dried to obtain a single mesoporous silica nanobowl.
3. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The mass ratio of the 1,3,5-trimethylbenzene in step (2) to the block copolymer F127 in step (1) is 1:0.33-10.
4. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The mass ratio of the tetraethyl orthosilicate in step (3) to the block copolymer F127 in step (1) is 1:0.33-10.
5. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The mass ratio of the dimethyldimethoxysilane in step (4) to the block copolymer F127 in step (1) is 1:0.17-5.
6. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: In step (5), evaporate at room temperature for 12-48 hours.
7. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The centrifugal speed in step (5) is 30000-80000 r / min, and the centrifugal time is 10-30 min.
8. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The washing conditions in step (5) are to first use distilled water for 3 times, and then use 95% ethanol solution for 3 times.
9. The method for preparing a single mesoporous silica nanobowl according to claim 2, characterized in that: The reflux temperature in step (5) is 50-90°C, and the reflux time is 0.5-5 h.
Citation Information
Patent Citations
Nano-silicon dioxide hollow sphere material and method of preparing the same
CN101343065A
Preparation of periodic mesoporous organic silicon oxide material
CN101475190A
Ordered mesoporous silicon-dioxide-substrate fluorescence nanometer material and preparing method thereof
CN101525533A
Hollow bowl-shaped silicon dioxide nanoparticles, preparation method and application thereof
CN106629747A
Hollow inorganic particle material, method for producing same, inorganic filler, slurry composition and resin composition
WO2023175994A1